Davutoglu, Ahmet. “Philosophy and Politics: A Comparative Study between the Islamic Theory of Tawḥīd (Oneness) and the Western Theory of Existence,” Translated by Ibrahim al-Bayoumi Ghanem. Year 4, Issue 16 (Spring 1419 AH/ 1999 CE), Pp. 47-97. - أوغلو أحمد داود; غانم إبراهيم البيومي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1999)
Ahmet Davutoglu’s article discusses the dissonance between Islamic and Western theoretical, philosophical, and cultural foundations and political visions through a specific framework of inter-relationships between ontology, epistemological theory, and the study of political values. He explores the origins of the problem in the foundation of each side’s worldview, and the extent to which the authenticity of the Islamic foundations is connected with the religious ontology that is based on belief and tawḥīd (Oneness of God). Moreover, he examines the difference between epistemological levels through existential ranks and epistemological theory, starting from its world view, and culminating in the value foundations of the political visions and cultures. He discusses the process of legitimizing political authority on the basis of epistemological tawḥīdic values, and the Western challenge towards Islamic societies and civilization